OPTIMALISASI POTENSI WISATA (GUA SUMUR, GUA KELELAWAR DAN GUA PRABU) DI DESA PRABU, KECAMATAN PUJUT, LOMBOK TENGAH - I., Johan Trinanda Hermawan; D., Arya Wiradana M.; Kafrawi, Achmad Evin; Amanda, Wira Risky; Kibtiah, Kamariatul; Rahayu, Widya; Tassya, Thania Olang; A., Bq. Dina Ayuni; Putri, Listia; Arifathiyah, Meylia; Rohadi, Rohadi (Jurnal Wicara, 2023)
Tourism is a recreational activity carried out with the intention of breaking away from the daily routine for a while. The tourist village is a combination of natural attractions, culture and creativity of the local community, supported by facilities that can attract tourists to visit the place. Prabu Village is one of the tourist destinations in Pujut District, Central Lombok. Even though it has advantages in natural beauty, unfortunately Prabu Village is still lacking in management and public awareness of the importance of existing tourism potential. Therefore, Unram Thematic KKN participants carried out community service in Prabu village with the theme 'Tourism and the Environment'. The purpose of this service is to introduce the tourism potentials in Prabu Village to the wider community. One of the programs carried out was by making a promotional video for Prabu Village which explained all the potential that the village had. Videos that have been made are then published on various social media (Youtube, Instagram, etc.), websites, and video platforms. With an effective promotional video, Prabu Tourism Village is expected to become an attractive tourist destination for both local and international tourists.